O Método Terapia Ocupacional Dinâmica e o Modello Vivaio: histórias orais de construções inventivas para a prática de terapia ocupacional - Mello, Ana Carolina Carreira de (2023)
Occupational therapy, regarded as a paradigmatic profession, originated amidst progressive movements in the early twentieth century in the United States, ushering in its own paradigm focused on healthcare through occupations. However, its expansion globally and in Brazil occurred under another paradigmatic logic, that of rehabilitation. In this scenario, compounded by tensions stemming from the dominance of the biomedical field in healthcare, Brazilian occupational therapists were driven to seek new ways of conceptualising their practice. Among these professionals, Jô Benetton stands out. In the 1970s, she initiated a research project culminating in the development of the Dynamic Occupational Therapy Method (MTOD). In Italy, also between the 1970s and 1980s, a group of professionals began practising occupational therapy under the framework of Psychoanalysis, opposing the prevalent protocol-driven and behavioural approaches of the time, and initiating the construction of the Modello Vivaio. Both theoretical-methodological proposals align with the initial paradigm of the profession, and while they are publicly known, their construction processes are relatively unknown, potentially offering insights for contemporary knowledge and professional development. Thus, the research question posed is: "What can be gleaned from the investigative processes developed by Jô Benetton, in collaboration with Sonia Ferrari, Julie Cunningham Piergrossi, and Carolina de Sena Gibertoni, which led to the development of MTOD and Modello Vivaio?" This study aimed to comprehend the construction of two theoretical-methodological proposals in occupational therapy that challenge hegemonic knowledge, with the objective of historically situating the authors' contributions to the profession from an epistemological perspective. Drawing on the ideas of John Dewey's Pragmatism, the study sought to reflect on modes of knowledge aimed at solving issues related to occupation. This framework presents itself as a theoretical-philosophical structure aimed at integrated problem resolution, considering the situation as a whole. Its complexity is incorporated by not distancing itself from primary experience, facts, or objects of everyday experiences, indicating the existence of other possibilities for constructing knowledge useful for practice. Supported by the life history oral methodology, rounds of interviews were conducted with the authors and collaborators, resulting in the construction of 42 narratives. These results were discussed considering knowledge construction processes that resist automatism and the invasion of bureaucracy and productivity in the space of thinking and investigating. This approach avoids separating the spheres of knowledge production and care production, based on the composition of theoretical outputs tied to practice, emerging from our field's coherence in unique ways of perceiving the world, valuing freedom in constructing a science that dances in contrast to more rigid and standardised approaches. Our discussion also asserts that occupational therapy produces joy and pleasure in constructing spaces that support health even in the face of confronting diseases and other difficulties. We outline the contours and limits of oral history research and emphasise the relevance of investigations involving MTOD and Modello Vivaio, as well as research that positions practice as an object of study. We hope that the insights about the possibilities of constructing knowledge in occupational therapy contribute to the epistemic debate in our field, restoring relationships between practice and theory. Furthermore, we also hope that this work can honour, albeit partially, the life efforts invested in these constructions, with the elegance they deserve.